Fertility Motivations and their Relation with Attitude towards Government Incentives for Childbearing in Women of Reproductive Age - zahra zare; Ehsan saffari (Journal of Mazandaran University of Medical Sciences, 2018)
Background and purpose: In recent years a severe decline occurred in fertility rates in Iran, therefore, policy makers changed demographic policies since 2012 and provided incentives for families. The purpose of this study was to investigate the relationship between fertility motives and attitudes toward government incentives that could promote childbearing in women in fertility ages. Materials and methods: This cross-sectional study was performed in 450 women (18- 35 years of age) attending health centers in Sabzevar, Iran 2016, using convenience and cluster samplings. The inclusion criteria were being married and not pregnant at the time of study. Demographic information was recorded and data was collected using Childbearing Motivations Scale and the scale for Attitude towards Governmental Incentives on Childbearing. Data analysis was done applying descriptive statistics, Pearson correlation tests, Spearman, and Kruskal Wallis test. P value of ≤ 0.05 was considered to be significant. Results: There was a significant direct correlation between the positive fertility motivation and free mother and child insurance (P= 0.004), free monthly check-ups, free pregnant mothers' food coupon (P= 0.01), and increased maternal leave (P= 0.01). In current study, a significant reverse correlation was found between negative fertility motivation and offering gold (P= 0.01), home mortgage and loans (P= 0.001), providing home (P= 0.001), and paternity leave (P= 0.004). Conclusion: According to this study government incentives on childbearing must focus on major effective factors on fertility motivation i.e. free mother and child insurance, offering gold, home mortgage and loans, and providing homes to the families.